2019
DOI: 10.1021/acsami.9b17825
|View full text |Cite
|
Sign up to set email alerts
|

High Efficiency Doping of Conjugated Polymer for Investigation of Intercorrelation of Thermoelectric Effects with Electrical and Morphological Properties

Abstract: Intercorrelation of thermoelectric properties of a doped conjugated semiconducting polymer (PIDF-BT) with charge carrier density, conductive morphology, and crystallinity are systematically investigated. Upon being doped with F4-TCNQ by the sequential doping method, PIDF-BT exhibited a high electrical conductivity over 210 S cm–1. The significant enhancement of electrical conductivity resulted from a high charge carrier density, which is attributed to the effective charge–transfer-based integer doping between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…To demonstrate the general applicability of the developed hybrid doping method, we applied the method to a different CP, PIDF-BT (Figure 7a), having a relatively lower degree of crystallinity and in the film and higher degree of CT with F4-TCNQ compared to P3HT. [54,55] It has been reported that sequentially doped PIDF-BT film exhibited a high σ 4P of 240 S cm −1 owing to the efficient dopant (F4-TCNQ) diffusion through the free volume of the amorphous domains (c.f. σ of PIDF-BT film doped by the mixture blending process is 5.0 S cm −1 ).…”
Section: Application Of Hybrid Doping To the Isoindoloindole-based Comentioning
confidence: 99%
“…To demonstrate the general applicability of the developed hybrid doping method, we applied the method to a different CP, PIDF-BT (Figure 7a), having a relatively lower degree of crystallinity and in the film and higher degree of CT with F4-TCNQ compared to P3HT. [54,55] It has been reported that sequentially doped PIDF-BT film exhibited a high σ 4P of 240 S cm −1 owing to the efficient dopant (F4-TCNQ) diffusion through the free volume of the amorphous domains (c.f. σ of PIDF-BT film doped by the mixture blending process is 5.0 S cm −1 ).…”
Section: Application Of Hybrid Doping To the Isoindoloindole-based Comentioning
confidence: 99%
“…As the degree of diffusion of the doping solution into the polymer matrix is deteriorated significantly because of the tightly inter‐packed chain configuration within the crystalline domain, [ 27 ] sequential doping was conducted with as‐cast films of the CPs without thermal annealing. The CP films were formed from partially nonvolatile o ‐dichlorobenzene (DCB, b.p.…”
Section: Resultsmentioning
confidence: 99%
“…Compounds 1, 1,2‐bis(5‐(trimethylstannyl)thiophen‐2‐yl)ethene, (3,3′‐difluoro‐[2,2′‐bithiophene]‐5,5′‐diyl)bis(tri‐methylstannane) and 5,5′‐bis(trimethylstannyl)‐2,2′‐bithiazole were prepared according to previously described procedures. [ 27,34–36 ] Detailed chemical structure and synthetic procedures are summarized in Supporting Information, and the molecular weight of obtained CPs was determined by gel permeation chromatography (GPC, Figure S11, Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…PIDF‐BT containing the IDID moiety has recently been reported to exhibit an outstanding electrical conductivity of >240 S cm −1 upon the implementation of diffusion‐controlled F4TCNQ doping, due to its strong electronic coupling with F4TCNQ. [ 23,24 ] Thus, PIDF‐BT was adopted as a molecular doping platform to quantitatively compare the doping efficiency, and the effectiveness of the devised doping strategy was demonstrated by the cascade doping of F4TCNQ in acetone, followed by NOBF 4 or AuCl 3 treatment in separate acetone and acetonitrile, respectively ( Figure a). After immersing the as‐cast PIDF‐BT film in each dopant solution for 10 s, the current density ( J ) versus electric field ( E ) characteristics were monitored using two‐terminal electrodes to compare the electric response of each doped film under an applied bias (Figure 1b).…”
Section: Figurementioning
confidence: 99%